The potential of amylase enzyme activity against bacteria isolated from several lakes in East Java, Indonesia: - INDAH KHOIRUN NISA; Prabaningtyas Sitoresmi; BETTY LUKIATI; RINA TRITURANI SAPTAWATI; ACHMAD RODIANSYAH (Society for Indonesian Biodiversity, 2021)
Abstract. Nisa IK, Prabaningtyas S, Lukiati B, Saptawati RT, Rodiansyah A. 2021. The potential of amylase enzyme activity against bacteria isolated from several lakes in East Java, Indonesia. Biodiversitas 21: 42-49. Indonesia is one country that has water resources having an abundance of microbial diversity, but not explored massively. This study aims to measure the amylase activity quantitatively from 53 amylolytic bacterial isolates from Ranu Pani, Ranu Regulo, Ranu Grati, and Ngebel Lake; also it identifies the isolate with the highest amylase enzyme activity. The amylase enzyme activity test calculates with DNS (Dinitrosalycylic acid) method, molecular identification of the highest bacterial isolate is based on the 16S rRNA gene. Its relationship is determined through the phylogenetic tree with the Neighbor-Joining (NJ) method. The results showed that the fifty-three bacterial isolates have amylase activity about 0.000-0.016 units/mL. The KN bacterial isolate from Ranu Ngebel was the highest amylase activity, producing enzyme around 0.016 units/mL, while isolate G20 from Ranu Grati was the lowest, reaching about 0.0001 Unit/mL. Based on the morphological and molecular identification, the KN bacterial isolate is classified as the Bacillus cereus group with 99.4-100% sequence similarity, closely related to Bacillus paramycoides (NR 157734.1).